ANALYSIS OF MEANS AND METHODS OF STRESS-STRAIN STATE CONTROL OF STRUCTURES DURING OPERATION - Devyatov, Ivan; Iurgenson, Sergei; Zharenov, Ivan; Trutnenko, Andrei; Tuev, Dmitrii (Journal of Applied Engineering Science, 2020)
This article defines the basic set of means and methods of the structural health monitoring of metal structures and structures from polymer composite materials (PCMs) used in the construction and aviation industry. The analysis of means and methods of strain-stress state control of a structure during operation (detection of defects and crack growth) and their comparison is provided.
Keywords: structural health monitoring systems, non-destructive testing, metal structures, polymer composite material structures, structural strength.